Building social intelligence scale and applied to a sample at the Deprived and non-Deprived students from their parents at the Secondary stage (Journal of the College of Education for Women, 2019)
The current research aims to :•know the level of social intelligence of the sample as a whole .. •taraf statistically significant differences in social intelligence between disadvantaged andnon-disadvantaged peers .To achieve these objectives, the selected sample of Talbhalmrahlh medium and specificallystudents of the second grade average, were chosen randomly stratified's (360) studentsincluded sex (male, female) and (deprived of the Father and the non-deprived) for theacademic year (2013-2014) for the province of Baghdad on both sides (Rusafa-Karkh (As applied to them measurements of social intelligence, which is prepared by the researcher,having achieved _khasaúsma of psychometric (valid and reliable .(When analyzing the data were used statistical methods, both when extracting multiplepsychometric properties, crashes or achieve the objectives of the research, including (Pearsoncorrelation coefficient, and the equation Alvakronbach and samples t-test for one sample andsamples t-test for two independent samplesThe researcher found the following results :.•eetmta the sample of students from the middle school social intelligently .•The existence of statistically significant differences in social intelligence among adolescentsdeprived of their parents and their peers who live with their parents, and in favor of the nondeprivedparents .In light of the findings of the researcher made a number of recommendations and suggestions.